Empowerment of Hotong and Ina Labuang Farmer Groups Through Dissemination of Technology and Innovation in Hotong Buru Processing (Seteria Itallica): Pemberdayaan Kelompok Tani Hotong dan Ina Labuang Melalui Diseminasi Teknologi dan Inovasi Pengolahan Hotong Buru (Seteria Itallica) - Siahaya, Griennasty Clawdya; Hanni Tuhuteru; Joselina Tuhuteru; Elia Radianto; Yohana Sutiknyawati Kusuma Dewi; Oke Anandika Letari; Komariyati, Komariyati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Hotong buru (Setaria italica) is one of the local food crops that has so far been traditionally processed to produce hotong seeds and the products produced are still limited to cake products that are consumed by the surrounding community. The limitations of processing infrastructure, knowledge, and skills in innovating from post-harvest to the diversity of hotong products are experienced by two (2) groups/partners in Labuang village, namely the Hotong Labuang Farmer Group and the Ina Labuang Group. The purpose of the service activities carried out is to answer partner problems related to limited processing infrastructure, knowledge, and skills in producing hotong products through collaboration in the development and application of science and technology produced by universities to be utilized for the needs of the community (partners). The solutions provided for the community, in this case, the partners, include technology dissemination starting from post-harvesting hotong to processing into products with packaging and marketing strategies. The method of implementing this service activity is through the KOSABANGSA program which starts from the stages of preparation, implementation monitoring, and evaluation. The results obtained in this service were achieved based on the designed activity plan where there was an increase in partner knowledge, partners were skilled in operating the technology tools provided such as dome, thresher, disk mill, processing of mosef flour, making cookies and noodles to the marketing strategy.